2020
DOI: 10.1111/pedi.13107
|View full text |Cite
|
Sign up to set email alerts
|

Educational outcomes among children with type 1 diabetes: Whole‐of‐population linked‐data study

Abstract: Background: Challenges with type 1 diabetes (T1D) blood glucose management and illness-related school absences potentially influence children's educational outcomes. However, evidence about the impact of T1D on children's education is mixed. The objectives were to estimate the effects of T1D on children's educational outcomes, and compare time since T1D diagnosis (recent diagnosis [≤2 years] and 3 to 10 years long exposure) on educational outcomes. Methods: This whole-of-population study used de-identified, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
2
17
1
Order By: Relevance
“…Other studies found no difference in exam GPAs, 14 and two population-based studies found no differences in national test scores between individuals with and without T1D. 11,15 Differences in outcome measures may partly account for some of the inconsistency between studies, for example, assessments versus final exams. Contrary to the existing literature, 11,14-17 we found that T1D is associated with an increased risk of not completing compulsory school.…”
Section: Educational Achievementmentioning
confidence: 94%
See 3 more Smart Citations
“…Other studies found no difference in exam GPAs, 14 and two population-based studies found no differences in national test scores between individuals with and without T1D. 11,15 Differences in outcome measures may partly account for some of the inconsistency between studies, for example, assessments versus final exams. Contrary to the existing literature, 11,14-17 we found that T1D is associated with an increased risk of not completing compulsory school.…”
Section: Educational Achievementmentioning
confidence: 94%
“…We confirm the negative association between HbA1c and educational outcomes found in previous studies. 11,12,14,15 Chronic hyperglycaemia is associated with changes in the grey matter volume of the brain and disturbed sleep. Acute dysregulations during tests have been found to be associated with worse academic test scores.…”
Section: Glycemiamentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study conducted in South Australia evaluated educational outcomes in children with T1D while also comparing the effect of times from T1D diagnosis (<2 years vs. 3–10 years). This study did not show differences in educational outcomes between children with T1D and controls, regardless of time since diagnosis [14].…”
Section: Influence Of T1d On Cerebral Structure and Cognitive Functionmentioning
confidence: 99%